2022
DOI: 10.1002/jlb.5a0721-396rr
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of T Cells in NK-AML(M4/M5) Revealed by Single-Cell Sequencing

Abstract: Normal karyotype acute myeloid leukemia (NK‐AML) is a highly heterogeneous malignancy that resides within a complex immune microenvironment, complicating efforts to reveal the interaction between leukemia cells and immune cells. Understanding tumor‐infiltrating T cells is crucial to the advancement of immune therapies and the improvement of the prognosis for NK‐AML patients. We performed single‐cell RNA sequencing on bone marrow cells from 5 NK‐AML (M4/M5) patients and 1 normal donor and paired single‐cell T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Several of these are known to be responsible for maintaining the stem-like state of the progenitor exhausted CD8 T cells. LYL1 is responsible for stem / progenitor state and self-renewal in thymocytes and T cells [31, 32, 33]. BCL11A slows differentiation of T cells to maintain self-renewal [34].…”
Section: Resultsmentioning
confidence: 99%
“…Several of these are known to be responsible for maintaining the stem-like state of the progenitor exhausted CD8 T cells. LYL1 is responsible for stem / progenitor state and self-renewal in thymocytes and T cells [31, 32, 33]. BCL11A slows differentiation of T cells to maintain self-renewal [34].…”
Section: Resultsmentioning
confidence: 99%
“…Contradictive to previous findings, a case-report study of 5 AML patients reported quite opposite findings in terms of accumulation of MAIT cells in bone marrow. 37 Finally, tumour cells might possess the capacity to stimulate MAIT cells, leading to their activation, exhaustion and their eventual depletion. This hypothesis is supported by the fact that myeloma cell lines do express MR-1 on their surface membrane and therefore can activate MAIT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, flow cytometric analysis of nine suspensions of lymph nodes from patients both with haematological diseases and patients with no histologically confirmed malignancy did not show significant accumulation of MAIT cells. Contradictive to previous findings, a case‐report study of 5 AML patients reported quite opposite findings in terms of accumulation of MAIT cells in bone marrow 37 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent article ( 14 ) described the clonal expansion of MAIT cells in the BM of patients with a specific subtype of AML (NK AML M4/M5). Intriguingly, the only patient not achieving complete remission showed a larger MAIT cell infiltration and expression of a specific gene transcription signature.…”
Section: Mait Cells In Hematologic Malignanciesmentioning
confidence: 99%